2023
DOI: 10.22541/essoar.168695523.32925211/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Soil Organic Carbon in Wildfire-Affected Areas of the McKenzie River Basin, Oregon, USA

Abstract: Large-scale wildfires are increasing in frequency and are likely to become more severe under future Pacific Northwest climate scenarios. The effects of wildfires on soil organic carbon (SOC) remain difficult to estimate because soil heterogeneity limits generalizations. We mapped fired severity within the footprint of the Holiday Farm Fire (McKenzie River, Oregon, 2020) and sampled a burn severity gradient (unburned, low, high) in a detailed scheme to account for inter- and intra-site variation (20 soil profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…So, a decrease in soil organic matter and loss of vegetation post-fire would likely mute this flushing behavior, resulting in decreased DOC during the wetting period. A post-fire soil study in the McKenzie sub-basin found that total soil organic carbon was decreased along a burn severity gradient (Katz et al, 2023). Other studies have also proposed decreased soil organic stocks as the cause of decreased DOC observed post-fire in California and Alaska, USA (Betts and Jones, 2009;Santos et al, 2019).…”
Section: Wildfire Decreased Variability Of Doc Concentrations and Led...mentioning
confidence: 99%
See 1 more Smart Citation
“…So, a decrease in soil organic matter and loss of vegetation post-fire would likely mute this flushing behavior, resulting in decreased DOC during the wetting period. A post-fire soil study in the McKenzie sub-basin found that total soil organic carbon was decreased along a burn severity gradient (Katz et al, 2023). Other studies have also proposed decreased soil organic stocks as the cause of decreased DOC observed post-fire in California and Alaska, USA (Betts and Jones, 2009;Santos et al, 2019).…”
Section: Wildfire Decreased Variability Of Doc Concentrations and Led...mentioning
confidence: 99%
“…However, this was likely not the case in our basin due to the mixed severity burn of the Holiday Farm fire, including ~63 % of the area burning at moderate to high burn severity. Moreover, research in high burn severity sites across the Holiday Farm fire area, found evidence of decreases in the percentage of soil organic carbon in the first 2 cm of soil (56 % change) and in the particulate organic carbon fraction (61 % change, Katz et al, 2023). The lack of a fire signal on the DOC concentrations may be related to the thick and active organic horizons and extremely high rates of saturated hydraulic conductivity in soils of the Pacific Northwest (Jarecke et al, 2021), which would have enabled infiltration and vertical percolation of water and DOC through the soil profile despite the burn.…”
Section: Spatial Stream Network Models Of Docmentioning
confidence: 99%